Hydrogen Production via Ice Electrolysis - Zainal Abidin, Muhammad Anas Bin (UNIVERSITI TEKNOLOGI PETRONAS, 2009)
Achieving a sustainable energy system obviously is an important goal of all societies. However, achieving that goal is complicated by multiple players with divergent interests promoting their views in the context of numerous complex technological considerations. This report basically discusses the project research done and basic understanding of the chosen topic, which is Hydrogen Production via Ice Electrolysis. The objective of the project is to do a research and verify that ice electrolysis is a more economic approach or method to produce and obtain hydrogen for multipurpose. The challenge of this project is to generate and separate all the gasses from the ice using electrolysis system which is to obtain oxygen and also hydrogen. The separation using electrolysis is more difficult when the medium is water instead of ice cube which it will reduce the voltage or current used while electrolyzing to produce hydrogen gas. When the electrolysis is in process, the voltmeter will show the usage of the voltage while electrolyzing the ice cube which will verify the topic of the project. As shown in the results, the level of pressure of hydrogen increases as water level increases which means that hydrogen can be produced more using ice electrolysis.